Pre-and post entry learning of young technology firms: antecedents of objective and tacit knowledge and performance implications - Schwens, C; Kabst, Rüdiger

Self-Organization in Sensor and Actor Networks - Dressler, Falko
Self-organization is a rather fascinating concept that enables systems consisting of huge numbers of autonomously acting subsystems to perform a collective task. Moreover, self- organizing systems show an overall behavior that cannot easily be predicted or even preprogrammed in a scalable way. It was in the early 1960ies that people like Ashby and Eigen investigated self-organization properties in (natural) systems. Since these days, a great number of (technical) solutions have been developed, which, either on purpose or unintentionally, inherently the basic concepts of self-organization. The aim of this book is to investigate the concepts of self-organization in the context of autonomous sensor and actor networks. The primary objective is to categorize the basic self-organization methods and to survey techniques for communication and coordination in massively distributed systems according to the developed classification scheme. Basically, two possible approaches can be thought of for organizing this book. First, we could start analyzing sensor and actor network technology and figure out what basic mechanisms are employed and how these relate to self-organization. A second approach would be to introduce self-organization as a methodology, apparently used everywhere in our life (in nature and in technical systems), and afterwards to continue with technical issues in sensor and actor networks searching for previously learned self-organization methods. I decided to follow the second approach in order to keep the focus on self-organization while studying the term in the world of sensor and actor networks. The term self-organization is still often misunderstood and misinterpreted. Therefore, this textbook is intended to be a basis for a better understanding of the concepts of self-organization, especially in the domain of sensor and actor networks. It provides a stepwise introduction of definitions, methodologies, and corresponding techniques relevant in the context of self-organization. Recent advances in miniaturization and wireless communication enabled the development of low-cost sensor nodes. Additionally, new application domains of sensor and actor networks emerged that demand for huge numbers of interacting devices. Thus, the relevance of self-organization methods is rapidly increasing as it is considered the primary control paradigm for distributed and massively distributed systems. The reader will see that self-organization has a number of advantages compared to other control paradigms. So, it becomes possible to operate huge numbers of collaborating subsystems even in case of limited resources, unreliable communication, and in case of massive failures of single systems. Unfortunately, these advantages are accompanied by some rather annoying side effects such as the increasing complexity and a nondeterministic behavior. By using optimal combinations of the basic methods of self-organization, these disadvantages can be minimized to some extent. According to the objective of this textbook - to study sensor and actor networks - the most relevant domains of communication and coordination are deeply investigated based on well-known algorithms and mechanisms and a number of case studies. This includes networking aspects of medium access control, ad hoc routing, data-centric communication, and clustering techniques. Additionally, control mechanisms for cooperation, task and resource allocation, and collaborative actuation are investigated. The book is concluded by a brief introduction of the domain of bio-inspired algorithms. This study is included for two reasons. First, to demystify the term bio-inspired networking, and secondly, to show the capabilities of such bio-inspired approaches.

Einsatz von E-Portfolios zur Förderung von studentischen Lerngemeinschaften im Hochschulstudium. - Sporer, Thomas; Jenert, Tobias; Strehl, Bernhard; Noack, Patrick Ole (DeLFI Workshops)
Keywords: E-Portfolios; Lerngemeinschaften; Praxisgemeinschaften; Projektgruppen; Hochschulstudium; informelles Lernen

Learning about innovation and knowledge creation in higher education. - Sporer, Thomas; Jenert, Tobias; Reinmann, Gabi (4. Konferenz Professionelles Wissensmanagement - Erfahrungen und Visionen)

Semivirtuelle Lernumgebung zum wissenschaftlichen Arbeiten als Ergänzung des Studienangebots der Universität Augsburg - Heinze, Nina; Sporer, Thomas; Jenert, Tobias (Deutsche Gesellschaft für Informationswissenschaft und Informationspraxis: Tagungen der Deutschen Gesellschaft für Informationswissenschaft und Informationspraxis)
Keywords: Wissenschaftliches Arbeiten; Blended Learning; Tutoring

Student Learning Communities in the Project-Centered Study Program" Problem-Solving Competencies" - Sporer, Thomas; Heinze, Nina; Jenert, Tobias; Reinmann, Gabi
Keywords: Problem Solving Competencies; E-Portfolio

Begleitstudium Problemlösekompetenz (Version 2.0). Infrastruktur für studentische Projekte an Hochschulen - Sporer, Thomas; Reinmann, Gabi; Jenert, Tobias; Hofhues, Sandra (Studieren neu erfinden - Hochschule neu denken)

Fallstudie: Social Software im Hochschulstudium - Sporer, Thomas; Jenert, Tobias (Enterprise 2.0 - Planung, Einführung und erfolgreicher Einsatz von Social Software im Unternehmen)

p-Shell Rabi-flopping and single photon emission in an InGaAs/GaAs quantum dot - Ester, P.; Lackmann, L.; Hübner, M.C.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Bichler, M. (Physica E: Low-dimensional Systems and Nanostructures)
Very clean single photon emission from a single InGaAs/GaAs quantum dot is demonstrated by the use of a coherent optical state preparation. We present a concept for single photon emission, which uses p-shell Rabi-flopping followed by a sequence of relaxation and recombination. The proof of the (clean) single photon emission is performed by photon correlation measurements.
Keywords: Antibunching; Single photon emission; Rabi oscillation; Coherent manipulation

On the asymptotic variance in nonparametric regression with fractional time-series errors - Feng, Yuanhua (Journal of Nonparametric Statistics)

Modelling financial time series with SEMIFAR GARCH model - Feng, Yuanhua; Beran, J.; Yu, K. (IMA Journal of Management Mathematics)

Semiparametric Modeling of Stochastic and Deterministic Trends and Fractional Stationarity - Beran, Jan; Feng, Yuanhua; Franke, Günter; Hess, Dieter; Ocker, Dirk (Processes with Long-Range Correlations)

Local Polynomial Estimation with a FARIMA-GARCH Error Process - Beran, Jan; Feng, Yuanhua (Bernoulli)

Special Issue: Quantile Regression

Kundenbindung durch Weiterempfehlung? Eine experimentelle Untersuchung der Wirkung positiver Kundenempfehlungen auf die Bindung des Empfehlenden. - Eggert, Andreas; Helm, Sabrina; Garnefeld, Ina (Marketing ZfP)

Immigration policy and the labor market: the German experience and lessons for Europe - Zimmermann, Klaus F; Bonin, Holger; Fahr, Rene; Hinte, Holger

On the inverse relationship between unemployment and absenteeism: evidence from natural experiments and worker heterogeneity - Fahr, Rene; Frick, Bernd

Incentives to invest in the human capital of temporary agency workers - Schmidt, Stephanie; Thommes, Kirsten (German Journal of Human Resource Management)

Outsourcing HR functions. Development of an explanatory approach to firms'(non-existent) demand for personnel services - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Management Revue)

Kooperation und Konkurrenz in Personaldienstleistungsbeziehungen - Bähring, Katrin; Thommes, Kirsten (Kooperation und Konkurrenz)